The impact of webcast and internet word-of-mouth to corporate reputation in banking - Chang, H.-C. (2018)
Social networks have emerged and been used extensively. Companies are very optimistic about the marketing effectiveness of the social networking sites. In addition, consumers increasingly rely on online word-of-mouth to collect information as the basis for consumer decisions. Because of the rise of FinTech (Financial Technology), banks have also gained interest in this marketing platform of webcast streaming, and even hope to affect consumer preferences. Webcast streaming is a crucial part of social marketing and it is the most interactive one. However, the characteristics of the banking activity require higher moral regulations and privacy protections. It is worth exploring about what category of content should be broadcasted or what type of interactive mode should be applied by banking corporations, to achieve marketing effectiveness by webcast to increase corporate reputation. SPSS 18.0 will be applied to execute correlation analysis, reliability analysis and regression analysis in order to investigate the impact of "webcast" and "internet word-of-mouth" on "corporate reputation". The findings would help banks to understand whether it should enhance corporate reputation through the interactive mode of webcast and internet word-of-mouth. It further allows consumers to aware the corporate reputations and social responsibilities of banking.